AN ACT TO SUPPORT ONLY BREAST MILK FOR INFANTS - Nurmawati Nurmawati; Nurfadhilah Nurfadhilah (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2020)
Working mothers are sometimes likely to have no intention of breastfeeding their babies, including providing their babies with exclusive breastfeeding. This happened at a hospital in Banten Province, Indonesia, where working mothers tended to have no intention of meeting the needs of breast milk for their babies. Interventions to change intentions and attitudes were given, i.e., a program called Emo-Demo initiated by the Indonesian GAIN program. In this study, after the intervention was given, all respondents, including working mothers, intended to breastfeed their babies. By using a Likert scale to determine the attitudes of respondents, after statistical tests, there were differences in the attitudes of mothers before and after the intervention. This means that the Emo-Demo program had succeeded in changing the intentions and attitudes of mothers to give their babies exclusive breastfeeding.